2020
DOI: 10.1038/s41419-020-2250-5
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Exosome-transmitted miR-567 reverses trastuzumab resistance by inhibiting ATG5 in breast cancer

Abstract: Trastuzumab is commonly used in the treatment of human epidermal growth factor receptor-2 positive (HER-2+) breast cancer, but its efficacy is often limited by the emergence of chemoresistance. Recent studies indicate that exosomes act as vehicles for exchange of genetic cargo between heterogeneous populations of tumor cells, engendering a transmitted drug resistance for cancer development and progression. However, the specific contribution of breast cancer-derived exosomes is poorly understood. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(96 citation statements)
references
References 47 publications
2
94
0
Order By: Relevance
“…Taken together, these results suggested that Circ_0030998 promoted CRC cells proliferation and angiogenesis via miR-567. Previous studies showed that miR-567 could regulate KPNA4 21 , ATG5 22 and then inhibited tumor progression or chemoresistance. To explore the mechanism by which miR-567 inhibited CRC cells proliferation and angiogenesis, three miRNA databases were used to predict the potential target genes in the present study.…”
Section: Circ_0030998 Facilitated Crc Cells Proliferation and Angiogementioning
confidence: 98%
“…Taken together, these results suggested that Circ_0030998 promoted CRC cells proliferation and angiogenesis via miR-567. Previous studies showed that miR-567 could regulate KPNA4 21 , ATG5 22 and then inhibited tumor progression or chemoresistance. To explore the mechanism by which miR-567 inhibited CRC cells proliferation and angiogenesis, three miRNA databases were used to predict the potential target genes in the present study.…”
Section: Circ_0030998 Facilitated Crc Cells Proliferation and Angiogementioning
confidence: 98%
“…For instance, miR-199a and miR-9 released via EVs enhanced chemosensitivity in a combinatorial protocol with temozolomide, leading to a significant reduction in proliferation, migration, and invasion of glioma [ 136 , 137 ]. In breast cancer, the use of exosomal miR-567 proved to be an effective means of reversing resistance to trastuzumab by inhibiting ATG5 expression [ 138 ] and miR-134 increased cisplatin-induced apoptosis by enhancing sensitivity to anti-Hsp90 drugs [ 13 ]. In liver cancer, miR-122 was found to be remarkably effective in decreasing chemoresistance by downregulating three genes, ADAM10, IGF1R, and CCNG1, involved in tumorigenesis and drug sensitivity.…”
Section: Engineering Ev-based Cancer Therapymentioning
confidence: 99%
“…In contrast, miR-16 acts as a tumor suppressor and can restore trastuzumab and lapatinib sensitivity by suppressing Cyclin J (CCNJ) and Far Upstream Element Binding Protein 1 (FUBP1) in resistant BC [105]. The exosomal transfer of miR-567 was recently reported to reverse trastuzumab resistance in BC via Autophagy related 5 (ATG5) inhibition; thereby, its therapeutic addition may considerably improve and enhance patients' responsiveness to this drug [106]. Other miRNAs with oncogenic or tumor suppressor functions in anti-HER2 drug resistance can be found in Table 2.…”
Section: Mirnas Involved In Bc Resistance To Targeted Therapiesmentioning
confidence: 99%